Use of nontarget organism Chironomus sancticaroli to study the toxic effects of nanoatrazine - de Albuquerque, Felícia Pereira [UNESP]; de Oliveira, Jhones Luiz [UNESP]; dos Santos Machado, Leila [UNESP]; Richardi, Vinicius Sobrinho; da Silva, Mario Antônio Navarro; Pompêo, Marcelo Luiz Martins [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Carlos, Viviane Moschini [UNESP] (Springer Nature, 2021)
Atrazine was banned by the European Union in 2004, but is still used in many countries. Agricultural research employing nanotechnology has been developed in order to reduce the impacts to the environment and nontarget organisms. Nanoatrazine was developed as a carrier system and have been considered efficient in weed control. However, its toxicity must be verified with nontarget organisms. In this context, the aim of the present study was to investigate ecotoxicological effects of solid lipid nanoparticles (empty and loaded with atrazine) and atrazine on Chironomus sancticaroli larvae, evaluating the endpoints: mortality, mentum deformity, development rate and biochemical biomarkers. The contaminant concentrations used were 2, 470, 950, and 1900 μg L−1 in acute (96 h) and 2 μg L−1 in subchronic (10 days) bioassays. An environmentally relevant concentration of atrazine (2 μg L−1) presented toxic and lethal effects towards the larvae. The nanoparticles loaded with atrazine showed toxic effects similar to free atrazine, causing mortality and biochemical alterations on the larvae. The nanoparticle without atrazine caused biochemical alterations and mortality, indicating a possible toxic effect of the formulation on the larvae. In the acute bioassay, most concentrations of nanoparticles loaded with atrazine were not dose dependent for the endpoint mortality. Only the atrazine concentration of 470 μg L−1 was statistically significant to endpoint mentum deformity. The atrazine and nanoparticles (with and without atrazine) did not affect larval development. The results indicate that Chironomus sancticaroli was sensitive to monitor nanoatrazine, presenting potential to be used in studies of toxicity of nanopesticides.
Keywords: Aquatic organism; Atrazine; Ecotoxicology; Invertebrate; Nanotechnology